1989
DOI: 10.1038/bjc.1989.108
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties of ten human ovarian carcinoma cell lines: calibration in vitro against four platinum complexes

Abstract: Summary Ten human ovarian carcinoma cell lines have been studied as a potential in vitro screen for the development of novel anticancer platinum complexes. Lines have been established and developed both from solid and ascitic tumours, from pretreated and untreated patients, and are available at a range of in vitro passage numbers. The biological properties of the lines were consistent with them being human, epithelial and of ovarian carcinoma origin. Using a tritiated thymidine or leucine uptake method, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
90
1
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(96 citation statements)
references
References 24 publications
(21 reference statements)
4
90
1
1
Order By: Relevance
“…Details of their establishment and biological properties have been described previously (Hills et al, 1989;Kelland et al, 1993). In addition, variants with acquired cisplatin resistance have been generated by continuously exposing cells to increasing concentrations of drug (41M/ 41McisR, CHI/CH1cisR, A2780/A2780cisR) (Behrens et al, 1987;Kelland et al, 1992).…”
Section: Cell Linesmentioning
confidence: 99%
“…Details of their establishment and biological properties have been described previously (Hills et al, 1989;Kelland et al, 1993). In addition, variants with acquired cisplatin resistance have been generated by continuously exposing cells to increasing concentrations of drug (41M/ 41McisR, CHI/CH1cisR, A2780/A2780cisR) (Behrens et al, 1987;Kelland et al, 1992).…”
Section: Cell Linesmentioning
confidence: 99%
“…AMD473 has been selected for phase I clinical trials in the UK, which are due to commence in 1997. Cell culture A panel of 11 parent human ovarian carcinomas (SKOV-3, OV1-P, A2780, HX/62, PXN94, CHI, 41M, OVCAR3, LK1, LK2 and PAl) and acquired cisplatin (cisR)-resistant sublines (A2780cisR, 4lMcisR, CHlcisR) were used in this study (Hills et al, 1989;Kelland et al, 1993a;Mellish et al, 1994). Cells were maintained free of Mycoplasma and were grown as monolayers in Dulbecco's Modified Eagle Medium supplemented with 10% fetal calf serum (Imperial Laboratories, Andover, UK), 2 mM L-glutamine and 0.5 ,ug ml-1 hydrocortisone in a humidified 6% carbon dioxide, 94% air atmosphere.…”
mentioning
confidence: 99%
“…Unfortunately, it is only possible to culture ovarian cancer cells in a small percentage of cases, and almost exclusively from ascites, not from solid tumor biopsies. 27,28 We did not obtain any epithelial cell cultures from 41 solid ovarian tumor biopsies either, not even with cell culture conditions favoring epithelial cell growth. However, we have obtained fibroblast-like cell cultures from 38 (93%) of these biopsies.…”
Section: Discussionmentioning
confidence: 96%
“…However, a major obstacle to this approach in the case of human ovarian cancer is the difficulty of culturing ovarian tumor cells ex vivo from tumor biopsies, and, to a lesser extent, malignant ascites. 27, 28 We have shown that fibroblast-like cells can readily be cultured from human solid ovarian tumor biopsies, in contrast to epithelial ovarian tumor cells. The objective of our study was therefore to test the feasibility of using these fibroblasts as a vehicle for regional, intraperitoneal (i.p.)…”
mentioning
confidence: 99%